ALIH KODE DALAM FILM DAARIN WA GAIKOKUJIN - Isma Adini Putri; Hana Nimashita; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research discussed about the code switching in Darin Wa Gaikokujin movie. The aim of this research is to know the kinds of code switching in Darin Wa Gaikokujin movie and the function of code switching in Darin Wa Gaikokujin movie. The object of this research is the sentences which have code switching in Darin Wa Gaikokujin movie. This research is a qualitative research which used descriptive method. The results of this research indicate; there are three kinds of code switching in this movie, which are inter-sentential switching, intra-sentential switching and tag switching and then there are eight function of code switching, existing in the analysis of data, which include Reiteration, Aggravating massage, Personalization, Substitution, Emphasis, Clarification, Interjection, Parenthesis, Quotation dan Topic shift.Key Word : Code switching, Movie, Darin Wa Gaikokujin